Phz1 contributes much more to phenazine‐1‐carboxylic acid biosynthesis than phz2 in Pseudomonas aeruginosa rpoS mutant. (11th July 2019) - Sun, Longshuo; Chi, Xiaoyan; Feng, Zhibin; Wang, Kewen; Kai, Le; Zhang, Kailu; Cheng, Shiwei; Hao, Xiuying; Xie, Weihai; Ge, Yihe
Abstract: Pseudomonas aeruginosa PAO1, a common opportunistic bacterial pathogen, contains two phenazine‐biosynthetic operons, phz1 ( phzA 1 B 1 C 1 D 1 E 1 F 1 G 1 ) and phz2 ( phzA 2 B 2 C 2 D 2 E 2 F 2 G 2 ). Each of two operons can independently encode a set of enzymes involving in the biosynthesis of phenazine‐1‐carboxylic acid. As a global transcriptional regulator, RpoS mediates a lot of genes involving secondary metabolites biosynthesis in many bacteria. In an other previous study, it was reported that RpoS deficiency caused overproduction of pyocyanin, a derivative of phenazine‐1‐carboxylic acid in P. aeruginosa PAO1. But it is not known how RpoS mediates the expression of each of two phz operons and modulates phenazine‐1‐carboxylic acid biosynthesis in detail. In this study, by deleting the rpoS gene in the mutant PNΔ phz1 and the mutant PNΔ phz2, we found that the phz1 operon contributes much more to phenazine‐1‐carboxylic acid biosynthesis than the phz2 operon in the absence of RpoS. With the construction of the translational and transcriptional fusion vectors with the truncated lacZ reporter gene, we demonstrated that RpoS negatively regulates the expression of phz1 and positively controls the expression of phz2, and the regulation of phenazine‐1‐carboxylic acid biosynthesis mediated by RopS occurs at the posttranscriptional level, not at the transcriptional level. Obviously, two copies of phz operons and their differential expression mediated by RpoS might help P. aeruginosa adapt to its diverse environments and establish infection in its hosts.